Progress in waste valorization using advanced pyrolysis techniques for hydrogen and gaseous fuel production. (January 2021) - Foong, Shin Ying; Chan, Yi Herng; Cheah, Wai Yan; Kamaludin, Noor Haziqah; Tengku Ibrahim, Tengku Nilam Baizura; Sonne, Christian; Peng, Wanxi; Show, Pau-Loke; Lam, Su Shiung
Highlights: We review the current pyrolysis technology for hydrogen and gas fuel production. Advanced pyrolysis is promising for sustainable hydrogen and gas fuel production. Microwave and solar pyrolysis are energy efficient among the advanced pyrolysis. CO2 pyrolysis is attractive carbon-negative technique of producing CO-rich syngas. More understanding of the reaction mechanism and process parameters is needed. Abstract: Hydrogen and gaseous fuel derived from wastes have opened up promising alternative pathways for the production of renewable and sustainable fuels to substitute classical fossil energy resources that cause global warming and pollution. Existing review articles focus mostly on gasification, reforming and pyrolysis processes, with limited information on particularly gaseous fuel production via pyrolysis of various waste products. This review provides an overview on the recent advanced pyrolysis technology used in hydrogen and gaseous fuel production. The key parameters to maximize the production of specific compounds were discussed. More studies are needed to optimize the process parameters and improve the understanding of reaction mechanisms and co-relationship between these advanced techniques. These advanced techniques provide novel environmentally sustainable and commercially procedures for waste-based production of hydrogen and gaseous fuels.